Adjuvant therapy in patients with ductal carcinoma in situ of the breast: The Pandora's box. (April 2017) - Lazzeroni, Matteo; Dunn, Barbara K.; Pruneri, Giancarlo; Jereczek-Fossa, Barbara Alicja; Orecchia, Roberto; Bonanni, Bernardo; DeCensi, Andrea
Highlights: Post-lumpectomy RT for DCIS reduces recurrences by 50%, even in the low-risk patients. ET provides risk reduction by ≈30% both in the ipsilateral and contralateral breast. Old age is an established protective factor in DCIS. In low risk DCIS discuss individually the risk/benefit ratio of omitting RT. Consider a dose reduction if menopausal symptoms occur during tamoxifen. Abstract: Most patients with ductal carcinoma in situ of the breast (DCIS) are eligible for breast conservation treatment. The key management decision is whether to add radiotherapy and/or endocrine therapy to minimize the risk of a subsequent recurrence. Recent analyses indicating a lack of benefit in terms of breast cancer-associated mortality have suggested that more conservative approaches, omitting adjuvant therapy or even surgery, may be advisable in selected patients. These mortality observations are directly influenced by widespread use of mammographic screening which has opened a Pandora's box of subclinical DCIS and early invasive lesions. Confusion as to how aggressively such possibly indolent lesions should be treated has led to misunderstandings among patients and medical professionals. While awaiting further prospective evidence from clinical trials, we endorse an active treatment of DCIS as the standard of care. Our rationale is twofold: invasive recurrences are associated with an increase in breast cancer mortality, which is not the only relevant endpoint for DCIS. The benefit of complete surgical excision, adjuvant radiotherapy and endocrine treatment in preventing recurrence and invasive progression has been demonstrated in DCIS. The challenge now is how to identify DCIS patients who will not progress to invasive carcinoma even without complete excision and, at the other extreme, those patients at the highest risk who require mastectomy for local control. The current controversies over whether and which adjuvant therapy should be implemented can at least in part be addressed by developing effective doctor-patient communications that enable mutual understanding about the management of this biologically heterogeneous disease.